PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIA 1 SMA NEGERI 8 PEKANBARU - Tika Febrina; Zulkarnain '; Zuhri D ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is a class action research that aims to improve the learning process and to increase the student’s mathematics learning outcomes by applying Discovery Learning model. The subjects of this research are the student of class XI MIA 1 SMAN 8 Pekanbaru at second semester of academic years 2014/2015, which amounts to 35 students. This research consists of two cycles, each cycle consists of four stages: planning, implementation, observation, and reflection. Data collected through observation and learning outcomes test. Data analysis is done by observation data analysis and student’s mathematics learning outcomes data analysis. The action is successful if teacher’s activities and student’s activities increase in every meeting and the number of students who reach Minimum Mastery Criteria increases in every cycle. Observation data analysis showed that learning process in class XI MIA 1 SMAN 8 Pekanbaru has improved at each meeting. Student’s mathematics learning outcomes data analysis show that student’s mathematics learning increase before action and after action, that aims: (1) Amount students that reach behavior Minimum Mastery Criteria of confidence in base score is 25 students increase to 32 students at the first cycle and 35 students at the second cycle. For discipline, in base score is 29 students increase to 32 students at the first cycle and 34 students at the second cycle. For responsibility, in base score is 31 students at the first cycle and at the second cycle; (2) Amount students that reach knowledge Minimum Mastery Criteria in base score is 17 students increase to 22 students at the first cycle and 29 students at the second cycle; and (3) Amount students that reach skill Minimum Mastery Criteria in base score is 12 students increase to 16 students at the first cycle and 18 students at the second cycle. The result of this research showed that cooperative learning Discovery Learning model improve the learning process and increase the mathematics learning outcomes the students of class XI MIA 1 SMAN 8 Pekanbaru at second semester of academic years 2014/2015.Keywords: Mathematic learning outcomes, Discovery Learning, Class action research